Strategi Edukasi Efektif pada Masyarakat untuk Pencegahan Stunting di Tingkat Keluarga di Desa Karang Duwet, Winong, Boyolali: Penelitian - Afrianna Elya Nur Ishartani; Agil Arafi; Agus Setiawan; Aulia Ayu Sestiani4; Wahyuning Chumaeson (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Stunting is an underlying nutritional problem that has long-term effects on growth and cognitive and human resource quality. High prevalence rates of stunting are affected by various factors, including dietary levels, lower levels of parent education, and limited community knowledge and understanding regarding early stunting prevention. This activity is expected to enhance community knowledge and understanding, especially at the family and community levels, concerning effective approaches and strategies on stunting prevention and education. In achieving this objective, the research method involved using a qualitative approach by involving community service activities in socialization, counseling, discussion, and Q & A processes involving Karangduwet villagers in Winong District, Boyolali Regency. Results indicated that there was an increase in knowledge and understanding among villagers and especially among members involved in the PKK program concerning knowledge and understanding of stunting causes, the significance of attuned nutrition and environmental health, and community involvement in stunting prevention. Communicative and participating approaches and processes in health and educational programs are thus important and highly effective approaches intended to encourage community involvement and participation.